140 mmol/L of sodium versus 77 mmol/L of sodium in maintenance intravenous fluid therapy for children in hospital (PIMS): a randomised controlled double-blind trial. Issue 9974 (28th March 2015) - McNab, Sarah; Duke, Trevor; South, Mike; Babl, Franz E; Lee, Katherine J; Arnup, Sarah J; Young, Simon; Turner, Hannah; Davidson, Andrew
Summary: Background: Use of hypotonic intravenous fluid to maintain hydration in children in hospital has been associated with hyponatraemia, leading to neurological morbidity and mortality. We aimed to assess whether use of fluid solutions with a higher sodium concentration reduced the risk of hyponatraemia compared with use of hypotonic solutions. Methods: We did a randomised controlled double-blind trial of children admitted to The Royal Children's Hospital (Melbourne, VIC, Australia) who needed intravenous maintenance hydration for 6 h or longer. With an online randomisation system that used unequal block sizes, we randomly assigned patients (1:1) to receive either isotonic intravenous fluid containing 140 mmol/L of sodium (Na140) or hypotonic fluid containing 77 mmol/L of sodium (Na77) for 72 h or until their intravenous fluid rate decreased to lower than 50% of the standard maintenance rate. We stratified assignment by baseline sodium concentrations. Study investigators, treating clinicians, nurses, and patients were masked to treatment assignment. The primary outcome was occurrence of hyponatraemia (serum sodium concentration <135 mmol/L with a decrease of at least 3 mmol/L from baseline) during the treatment period, analysed by intention to treat. The trial was registered with the Australian New Zealand Clinical Trials Registry, number ACTRN1260900924257. Findings: Between Feb 2, 2010, and Jan 29, 2013, we randomly assigned 690 patients. Of these patients, primary outcome data were available for 319 who received Na140 and 322 who received Na77. Fewer patients given Na140 than those given Na77 developed hyponatraemia (12 patients [4%] vs 35 [11%]; odds ratio [OR] 0·31, 95% CI 0·16–0·61; p=0·001). No clinically apparent cerebral oedema occurred in either group. Eight patients in the Na140 group (two potentially related to intravenous fluid) and four in the Na77 group (none related to intravenous fluid) developed serious adverse events during the treatment period. One patient in the Na140 had seizures during the treatment period compared with seven who received Na77. Interpretation: Use of isotonic intravenous fluid with a sodium concentration of 140 mmol/L had a lower risk of hyponatraemia without an increase in adverse effects than did fluid containing 77 mmol/L of sodium. An isotonic fluid should be used as intravenous fluid for maintenance hydration in children. Funding: National Health and Medical Research Council, Murdoch Childrens Research Institute, The Royal Children's Hospital, and the Australian and New Zealand College of Anaesthetists.